Ultra-Low-Loss and Broadband All-Silicon Dielectric Waveguides for WR-1 Band (0.75–1.1 THz) Modules - Ratmalgre Koala; Ryoma Maru; Kei Iyoda; Li Yi; Masayuki Fujita; Tadao Nagatsuma (Photonics, 2022)
This study presents ultra-low-loss and broadband all-silicon dielectric waveguides for the WR-1 band (0.75–1.1 THz). The waveguides are built in high-resistivity silicon (10 kΩ-cm) and integrated with supportive frames fabricated from the same silicon wafer in a single etch process to achieve a compact design. We pursued low-loss, broadband, substrateless, unclad and effective medium waveguides. Smaller propagation losses of 0.3 dB/cm and 0.1 dB/cm were achieved for the unclad and effective medium waveguides, respectively. The 3 dB bandwidth was not encountered in the frequency range of interest and was as broad as 350 GHz. An unclad waveguide was employed to devise a Y-junction to demonstrate its practical applications in terahertz imaging. An integrated circuit card was successfully scanned. In addition, we developed unclad waveguide, effective medium waveguide, and Y-junction modules. The modules incorporated an input/output interface compatible with a standard WR-1 flange (254 μm × 127 μm). Unlike the conventional hollow waveguide modules, the unclad waveguide and effective medium waveguide modules reported total loss improvements of 6 dB and 8 dB, respectively, across the operation band. Our results provided a systematic way of achieving low-loss, compact, and versatile modules in the WR-1 band based on all-dielectric-waveguide platforms.